Hall operators on the set of formations of finite groups - Mekhovich, A.P.; Vorob’ev, N.N.; Vorob’ev, N.T. (Algebra and Discrete Mathematics, 2010)
Let π be a nonempty set of primes and let F be a saturated formation of all finite soluble π-groups. It is constructed the saturated formation consisting of all finite π-soluble groups whose F-projectors contain a Hall π-subgroup.